The Outputs of Retail Activities: Concepts, Measurement and Evidence from U.S. Census Data - Betancourt, Roger R.; Gautschi, David A. (The Review of Economics and Statistics, 1993)
The authors develop a new economic framework for the empirical analysis of retail margins. This framework formalizes the role of distribution services as outputs of retail activities. Their main results are the following: the measures of outputs of retail activities identified in the data perform as important and robust determinants of retail margins; variables that purport to capture oligopolistic features of market structure play a limited or no role in determining retail margins; quantity setting and price setting under the assumptions of profit maximization and monopolistic competition are categorically rejected by the data. The data base is information on 49 retail sectors from the 1982 U.S. Census of Retail Trades. Copyright 1993 by MIT Press.